Perancangan Enterprise Architecture Event Management System Dengan Metode TOGAF ADM: (Studi Kasus: PT SEKARMENUH EVENTAMA) - Muhammad Gilang Taufiq; Maulana Sidiq; Nana Yudi Permana (Jurnal Mahasiswa Sistem Informasi Galuh, 2026)
The event management industry encounters major challenges due to the complexity of organizing events and the absence of integrated systems. These limitations result in inaccurate data, slow processes, and decision-making barriers that undermine professionalism and competitiveness. PT. Sekarmenuh Eventama, as the case study, faces issues including the lack of a collaborative platform for budget approval (RAB), non-digitalized information, and limited real-time reporting. This study aims to design an information technology architecture based on Enterprise Architecture (EA) using the TOGAF framework to support event management systems. The focus lies in integrating event planning, execution, and evaluation while building an effective EA framework. A qualitative case study approach was applied in Denpasar, Bali, with data collected through interviews, observations, and literature studies. System design was developed using the TOGAF ADM framework up to Phase E (Opportunities and Solutions). The results deliver an integrated IT architecture blueprint covering business, application, data, and technology layers. The proposed business process model reduces manual work and provides application functions such as participant registration, vendor management, reporting, and event analysis. Findings show that TOGAF effectively improves data consistency and decision-making speed, although challenges remain in system integration and IT infrastructure readiness.